Developing, Implementation and Evaluation of Patient Safety Training Program for Nurses. - Komeili, Mohammad; Pazokian, Marzieh; Ilkhani, Mahnaz; Tondro, Amirhossein (Journal of Evidence-based Care, 2023)
Background: Complex medical condition, monitoring, treatment process and multitude devices in Intensive Care Unit (ICU) increase the risk of errors and unintended adverse events. So, Patient safety is important for ICUs nurses. Aim: The present study was performed with aim to develop, implement and evaluate patient safety training program for nurses. Method: This semi-experimental study with pretest and posttest design was conducted on 162 nurses recruited from the ICUs in three educational hospitals of Kermanshah University of Medical Sciences. To develop the program, the nurses’ needs were assessed using a patient safety questionnaire (84 items) developed based on WHO guideline on nine patient safety statement. After confirming validity and reliability, the questionnaires were distributed among nurses in rotation shifts and retrieved in the same shifts. After developing and implementing the program based on Kern's model, nurses’ knowledge and performance in patient safety measures was re-examined. The data were analyzed by SPSS (version 21) and independent and paired t-tests. Results: The mean score of patient safety knowledge of ICU nurses significantly increased from 51.48±34.35 before the intervention to 57.29±24.17 after the intervention (p<0.001). Also, the mean score of performance significantly increased from 42.53±30.64 before the intervention to 48.91±22.15 after the intervention (p<0.001). Implications for Practice: The implementation of the patient safety education program for ICU nurses was effective in improving their knowledge and performance of patient safety measures. So, the interventions based on educational model can provide the effective program according to time and cost.